Critical success factors for achieving superior m-health success. (9th April 2007) - Dwivedi, A.; Wickramasinghe, N.; Bali, R.K.; Naguib, R.N.G.; , S. Goldberg
Recent healthcare trends clearly show significant investment by healthcare institutions into various types of wired and wireless technologies to facilitate and support superior healthcare delivery. This trend has been spurred by the shift in the concept and growing importance of the role of health information and the influence of fields such as bio-informatics, biomedical and genetic engineering. The demand is currently for integrated healthcare information systems; however for such initiatives to be successful it is necessary to adopt a macro model and appropriate methodology with respect to wireless initiatives. The key contribution of this paper is the presentation of one such integrative model for mobile health (m-health) known as the Wi-INET Business Model, along with a detailed Adaptive Mapping to Realisation (AMR) methodology. The AMR methodology details how the Wi-INET Business Model can be implemented. Further validation on the concepts detailed in the Wi-INET Business Model and the AMR methodology is offered via a short vignette on a toolkit based on a leading UK-based healthcare information technology solution.